Community Health Empowerment Strategy Through The Smile and Greeting Program - Tri Yuliani (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2022)
This study aims to find out about how the Fajr congregation plans in empowering the community through the Smile Greetings and Salam program, to find out how the implementation of the Smile Greetings program in empowering the community, and to find out the results of the Smile Greetings program in empowering the community. The method used is a qualitative research with a descriptive approach. Sources of primary data obtained from observations and conducting interviews with the parties concerned. Secondary data sources were obtained from relevant documents and photos in this study. The results of this study prove that community empowerment that occurs in the first five people of the first five community members in the community empowerment program, there are curative and non-curative services. Curative is in the form of treatment while non-curative is in the form of health education to the community. The purpose of this research is to improve people's lives, especially in the form of daily mental needs.